A new view of integrating stratigraphic and tectonic analysis in South China Sea and north Borneo basins. (15th June 2019) - Lunt, Peter
Graphical abstract: Abstract: This review outlines how SE Asian tectonic and stratigraphic studies could be more closely linked. Many tectonic papers on the region include comments on stratigraphic evidence, and stratigraphic papers often allude to tectonic events, but this paper highlights the benefits of a more detailed integration of the two fields of study into a single geological model, by using inductive sequence stratigraphic methods supported by geohistory plots. The South China Sea and North Borneo region has been traditionally been divided into Provinces, each with its own distinct stratigraphy. A handicap in merging all the Provinces into one geological model has been the inconsistent application of basic biostratigraphy, and some examples are given that illustrate that more careful documentation of a complex data set is required in future work. The inductive stratigraphic method requires increased analytical work to calibrate seismic data, but even on current data an episodic stratigraphic history is indicated, and a single tectono-stratigraphic framework for the whole region is emerging, with a greatly simplified and consistent terminology. This review examines the impact of these methods on one important period of transition around the Oligo-Miocene boundary. The summary given for the Oligo-Miocene transition questions the viability of the commonly cited slab-pull tectonic model, as both the historical order of geological events and geographic spread of effects does not fit that model as currently understood.